THE BEHAVIOR, STABILITY PROPERTIES, AND POTENTIAL APPLICATIONS OF RHAMNOLIPID BIOSURFACTANTS IN OIL DEGRADATION (ASEAN Engineering Journal, 2023)
Rhamnolipid biosurfactants are among the most investigated for various applications, owing not only to their much lower environmental impact compared to chemical surfactants but also because they have proven effective in reducing surface tension and critical micelle concentration (CMC). However, there is concern regarding their high cost. This work aims to determine important behavior and properties of rhamnolipids and verify their potential for oil degradation. They were characterized using FTIR, 1H NMR, and 13C NMR spectroscopy to determine the main functional groups and the chemical structure of rhamnolipids for oil degreasing. Then, the influence of thermodynamic properties on CMC stability was studied to establish the stability behavior. This investigation is essential as good oil degreasing products require low CMC values to minimize the amount used during the oil removal process, form micelles, and solubilize dirt and oil. The oil degradation ability of rhamnolipids in different concentrations was studied using an oil dispersion test and the method of oil removal from a glass surface. Overall, this investigation proves that the temperature of the solution and immersion time influenced the CMC and surface tension value for the rhamnolipids. The lowest CMC value was 35 mg/L at 55 °C after 48 h of stabilization. The minimum recommended amount of rhamnolipids for the oil degrease formulation was also found to be 0.1% w/v, which is very low. This study showed that the behavior and stability of rhamnolipids are suitable for oil degradation applications and can efficiently replace chemical surfactants in oil degradation products.